(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
Employee turnover is a widely recognised subject in an organisational setting. Although academics and organisational human resource departments have accepted the fact that employee turnover can have a disastrous impact on the organisation, there are limited studies conducted on the causative factors and effects of employee turnover in organisations. Therefore, this study helped to highlight some of the causative factors triggering employee turnover and their impact on an organisation. In addition, the study also suggests vital strategies for mitigating and reducing employee turnover. In line with the preceding assertion, the cross-sectional qualitative study taking into consideration conference papers, government periodicals, chronological documents, and mainly secondary and primary sources were used. Online search engines such as Scopus, EBSCO, Emerald, science direct, and unrestricted web service search engines such as google scholar and Mendeley demonstrated to be valuable database resources. The finding indicated that performance appraisal feedback, job insecurity, stress and work overload, death, and compensation are significant factors responsible for employee turnover was also deduced that employee turnover can affect organisational performance through ineffectuality in the delivery of service, increase in workload, errors in work processes and reduction in sense of loyalty. However, findings also postulated that training and development, competitive benefits and compensation, effective leadership, and job satisfaction are key procedures that help in reducing and mitigating employee turnover.